Seasonality and distribution of epilithic diatoms in an Alkaline lake (Lake hazar, Elazig, Turkey) - Sonmez, Feray; Sen, Bulent (My University, 2011)
In this study, epilithic diatoms and their seasonal variations were determined from 4 stations along the south littoral of an alkaline lake (Lake Hazar) for a 1-year period. Temperature, pH, electrical conductivity, total hardness, dissolved oxygen, organic matter, nitrite, nitrate, orthophosphate, total phosphorus, sulphate, silica and chlorophyll a concentrations were measured and analysed. During the study, a total of 67 diatom taxa belonging to 30 genera were identified. Navicula spp. (10 taxa) were the most noticeable diatoms in terms of species numbers and numbers of individuals in the epilithon, followed by Cymbella spp. (7 taxa), Epithemia spp. (7 taxa) and Gomphonema spp. (6 taxa) at the stations. The diatoms showed their best growth in late-spring and summer, and they reached their highest numbers in summer. The diatoms occurred in low numbers in the other two seasons. The chemical and physical properties of the lake water were discussed in relation to seasonal occurrence of the diatoms. © by PSP.
Keywords: Alkaline lake; Distribution; Epilithic diatom; Lake hazar; Seasonal changes; Turkey